2019
DOI: 10.1536/ihj.18-723
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Dyssynchrony with Pharmacological Ablation of Right-Sided Accessory Pathway-Induced Cardiomyopathy in Infants

Abstract: Right-sided accessary pathways in patients with Wolff-Parkinson-White (WPW) syndrome may cause cardiac dyssynchrony and dilated cardiomyopathy, with a characteristic septal shape, irrespective of any supraventricular tachycardia episodes. We report on two infants (13 and 5 months), whose right-sided accessary pathway-induced dilated cardiomyopathy was successfully treated by flecainide for the first time. After the flecainide administration, an abnormal aneurysmal dilation of the basal interventricular septum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, the number of cases in these studies was small with uncertain efficacy. 5,6 Three patients in the present study had been treated with oral amiodarone for 14 to 30 days before RFCA with no efficacy. The potential hepatic and thyroid toxicity of amiodarone limits its use in infants with immature organs function.…”
Section: Efficacy Of Pharmacologic Therapy For Infantile Preexcitatio...mentioning
confidence: 88%
See 1 more Smart Citation
“…However, the number of cases in these studies was small with uncertain efficacy. 5,6 Three patients in the present study had been treated with oral amiodarone for 14 to 30 days before RFCA with no efficacy. The potential hepatic and thyroid toxicity of amiodarone limits its use in infants with immature organs function.…”
Section: Efficacy Of Pharmacologic Therapy For Infantile Preexcitatio...mentioning
confidence: 88%
“…4 Treatment with amiodarone, flecainide, or propafenone has been reported with inconclusive effects. 5,6 Although radiofrequency ablation (RFCA) could fundamentally improve the prognosis by successfully blocking ventricular preexcitation, the difficulty of ablation is much greater than that of children and adults due to factors such as small infant weight, small blood vessels, small heart chambers, high proportion of multiple pathways, and the risk of para-His pathway ablation. Therefore, this study aimed to investigate the clinical features, evaluate safety, and efficacy of RFCA for preexcitation-induced DCM in infants, and to aid the early diagnosis and therapeutic interventions for these patients.…”
mentioning
confidence: 99%
“…The dyskinesis of the interventricular septum at mid-systole was a frequent finding in 38 of 42 patients (90%). [13] ). (A) Aneurysmal dilation at the base of the interventricular septum seen in a 13-month-old male infant.…”
Section: Dyssynchrony and Geometrymentioning
confidence: 99%
“…Fig.6. A typical example of mechanical abnormality and morphological degeneration in preexcitation-induced cardiomyopathy (Sekine et al[13] ). (A) Aneurysmal dilation at the base of the interventricular septum seen in a 13-month-old male infant.…”
mentioning
confidence: 99%
“…If possible, measures such as marking and Catheter observation for proper catheter movement and passage, observation of plasma markers such as troponin, after ablation, and to ensure the presence or absence of possible damage and even to prevent catheter passage, used vessels with a diameter of less than 5mm. The incidence of such errors is very low and, for example, in one study, the incidence of coronary artery damage during ablation was reported to be around 0.09% [84] ; However, with all the reported risk factors and even with the possibility of av block due to the sudden death of cardiac cells and other risks of this disease, cryo or RF surgery is required, [85] the use of marking systems With advanced 3D mapping to find the exact signs of side paths, it can greatly contribute to the success of the surgery [75]. Also, in patients with venous occlusion problems or anatomical problems or even pregnancy, performing this surgery can face challenges.…”
Section: Novel Approaches In Drug Designing and Developmentmentioning
confidence: 99%